PETROLOGI DAN PETROGRAFI SATUAN BREKSI VULKANIK DAN SATUAN TUF KASAR PADA FORMASI JAMPANG, DAERAH CIMANGGU DAN SEKITARNYA, JAWA BARAT - Verdiana, Puteri Rasdita M.; Yuniardi, Yuyun; Nur, Andi Agus (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
The research area is located at Cimanggu Region, Langkaplancar and Pamarican Subdistrict, Ciamis, Tasikmalaya, and Pangandaran District, West Java Province. Geographically, research area located at coordinate 07o27’35,7768” to 07o32’35,7768” South Latitude and 108 o23’,482” to 108 o28’1,4844” East Longitude. Broad of research area is + 100 km2. According to unofficial lithostratiraphy, research area divided into five unit, that is Volcanic Breccia Unit, Coarse Tuff Unit, Carbonateous Sandstone Unit, Tuffaceous Sandstone, and Fine Tuff Unit.Petrology and petrography analysis of Volcanic Breccia Unit and Coarse Tuff Unit (Jampang Formation) are based on megascopic description of hand specimen sample and microscopic description of thin section. Volcanic Breccia Unit consist of volcanic breccia that composed by porphyry andecite-porphyry basalt clast with trachitic texture and crystal tuff as matrix, also porphyry andecite lava with trachitic texture and altered because secondary minerals (chlorite and secondary quartz) was identified at thin section. Coarse Tuff Unit consist of interbedding coarse tuff and fine tuff, but coarse tuff was dominant. Based on petrography analysis, coarse tuff is crystal tuff that composed by volcanic glass as matrix, and quartz and plagioclase as mineral fragment.